2022
DOI: 10.1177/15412040221111328
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Figure of Delinquency:New Evidence and Its Underlying Psychopathology

Abstract: Although research on the dark figure of delinquency has produced valuable quantitative estimates of its size, prior research is mechanistic and atheoretical about the conceptual underpinnings of the crimes that go undetected by the juvenile justice system. Drawing on data from 253 adjudicated youth in residential placements in the Midwestern United States, the current study found that youth self-reported over 25 delinquent offenses for every one police contact. The dark figure of delinquency has a wide distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Walters (2014) found evidence that difficult temperament had a significant indirect relationship with delinquency through its effects on maternal involvement and resulting externalizing behavior. Minkler et al (2022) found that temperament had a statistically significant relationship with the dark figure of delinquency (unreported delinquent acts). Those with more difficult temperaments had a greater dark figure of delinquency than their more well-regulated counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Walters (2014) found evidence that difficult temperament had a significant indirect relationship with delinquency through its effects on maternal involvement and resulting externalizing behavior. Minkler et al (2022) found that temperament had a statistically significant relationship with the dark figure of delinquency (unreported delinquent acts). Those with more difficult temperaments had a greater dark figure of delinquency than their more well-regulated counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%